2017
DOI: 10.1080/20013078.2017.1350088
|View full text |Cite
|
Sign up to set email alerts
|

Circulating exosome microRNA associated with heart failure secondary to myxomatous mitral valve disease in a naturally occurring canine model

Abstract: Myxomatous mitral valve disease (MMVD) is functionally and histologically identical to mitral valve prolapse (MVP) in humans. Currently, there are no medical treatments that can delay the progression of this valvular disease or associated cardiac remodelling. Therefore, there is a need to understand the molecular pathology associated with MMVD and MVP better, and thus identify potential therapeutic targets. Circulating exosomes contain small RNA, including miRNA, which reflect cell physiology and pathology. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
69
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 41 publications
0
69
1
Order By: Relevance
“…Dysregulation of the extracellular matrix appears to be central to these changes. Valvular interstitial cells, possibly with post‐transcriptional regulation from microsatellite ribonucleic acids, acquire properties of activated myofibroblasts, and activated myofibroblasts increase proteolytic enzymes, including matrix metalloproteinases, which degrade collagen and elastin faster than they can be produced by unactivated valvular interstitial cells …”
Section: Incidence Pathology and Pathogenesis Of Mmvdmentioning
confidence: 99%
See 3 more Smart Citations
“…Dysregulation of the extracellular matrix appears to be central to these changes. Valvular interstitial cells, possibly with post‐transcriptional regulation from microsatellite ribonucleic acids, acquire properties of activated myofibroblasts, and activated myofibroblasts increase proteolytic enzymes, including matrix metalloproteinases, which degrade collagen and elastin faster than they can be produced by unactivated valvular interstitial cells …”
Section: Incidence Pathology and Pathogenesis Of Mmvdmentioning
confidence: 99%
“…Systemic or local metabolic, neurohormonal, or inflammatory mediators (eg, endogenous catecholamines, inflammatory cytokines) also may influence progression of the valve lesion or the subsequent myocardial remodeling and ventricular dysfunction that accompany long‐standing, hemodynamically important valvular regurgitation. The interactions of these factors, as well as the impact of changes in mitral valve annular geometry and mechanical stress on the pathogenesis and progression of MMVD, are incompletely understood …”
Section: Incidence Pathology and Pathogenesis Of Mmvdmentioning
confidence: 99%
See 2 more Smart Citations
“…Exosomes are also suggested to deliver intracellular contents such as proteins and RNAs, functioning as message transporters to promote VC . Emerging evidences revealed that exosomal miRs were significant in diagnosis, prognosis or even therapeutic target selection in patients with cancer and heart failure . Selective enrichments of miRs in exosomes were due to the alterations in parental or donor cells, from which exosomes are secreted or originated .…”
Section: Exosomes Participate In Vcmentioning
confidence: 99%